Analysis of the Water Resources Sustainable Utilization in Guangdong Province and Nine Cities in the Pearl River Delta Based on Ecological Footprint Theory - ZHANG Yimin; ZHANG Xiaolin; CHEN Chang (Renmin Zhujiang)
This paper focuses on the coordinated development between water resources utilization and the economy in Guangdong Province.Utilizing the water ecological footprint model,it calculates the per capita water ecological footprint,ecological carrying capacity,and ecological surplus (deficit) of Guangdong Province and nine cities in the Pearl River Delta in the past 10 years in terms of production,life,and ecological water use.The results show that from 2011 to 2020,the water ecological footprint per capita in these areas has shown a downward trend,and water utilization efficiency has increased year by year.In the past 10 years,the per capita water resources carrying capacity is greater than the ecological footprint,and water resources are in a sustainable state.However,the ecological surplus has shown a slow downward trend.As the production water accounts for a large proportion of total water use,a considerable improvement in agricultural water saving can be achieved in the province.In the process of economic development,it is still necessary to strengthen the management of water resources to further improve the water use efficiency and promote the sustainable use of water resources in the province.